Iranian-Islamic Culture in ELT: Exploiting Shahnameh and Masnavi in Iranian TEFL - Faezeh Boroomand; Hosein Yazdani (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2017)
Regarding the requisite role of EFL learners' native culture alongside the target culture in TEFL in the globalization era, the present paper discusses the advantages of teaching EFL learners' national and local culture through local literature in TEFL and then elaborates on the potentiality of teaching Iranian-Islamic culture through Persian Literature in Iranian TEFL. Consequently, among many invaluable works of Persian Literature, Shahnameh and Masnavi are introduced as rich sources of Iranian-Islamic culture which can be employed in TEFL in Iran. Including the deep teachings of these two prominent works of Persian Literature in TEFL in Iran is one of the effective ways through which the Iranian-Islamic moral principles and attitudes can be fostered in EFL learners and the sublime messages of Ferdowsi and Mowlana can be passed down to the generations. Applying the idea will be beneficial not only to Iranian EFL learners during their language learning but also to the whole Iranian society in the long term.